Effectiveness of Peer Counseling Toward Mother’s Knowledge and Skills Among Gave Exclusive Breastfeeding in Cangkringan, Yogyakarta - Rizqiea, Noerma Shovie; Widyandana, Widyandana; Haryanti, Fitri (Universiti Putra Malaysia Press, 2022)
Introduction: Breastfeeding is a normal condition for babies to get the nutrients they need to grow and develop. Peer counseling is one way that can be used to help mothers in exclusive breastfeeding. The purpose of this research is to find of effect peer counseling on changes in the mother’s knowledge and skills of exclusive breastfeeding. Methods: The type of study is quasi-experimental research with pre and post-test design without control. The technique of sampling uses probability sampling with random cluster sampling. Samples taken from 5 villages in Cangkringan are 33 mothers breastfeeding infants aged 0- 6 months. This study was conducted from March to May 2016. The instrument used in this study was a questionnaire sheet about mothers’ knowledge about exclusive breastfeeding and an observation sheet for breastfeeding observation assistance. The data analysis used the Wilcoxon test because the data distribution did not normal. Results: The p-value obtained from the Wilcoxon test result is 0.000 (p<0.05) for the mother’s knowledge and the p-value of 0.012 (p <0.05) for the mother’s skills, which means that there are differences in knowledge and skills significantly between before peer counseling with after peer counseling. Conclusion: Mother’s knowledge and skills in exclusive breastfeeding can be increased by peer counseling.